KORELASI PANJANG TULANG EKSTREMITAS DENGAN TINGGI BADAN DALAM IDENTIFIKASI FORENSIK - Saputra, Satria (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2021)
The measurement of extremity bones length in forensic identification can be used to determine the personal identity , one of which is the stature. Several studies have been conducted to generate predictive regression formula, yet, each formula resulted different number of one’s stature including various methods of its measurement. This research aims to analyze the correlation between extremity bones length with stature, measurement methods, final result deviation, and which part of extremity bones has the strongest correlations. The articles were searched and collected from Google scholar and Sciencedirect.com by entering “extremity bone length and stature” as the keywords in which 25 qualified articles were reviewed based on the inclusion criteria under this research. In terms of upper extremity, 10 of 17 articles revealed a correlation between forearm/radius and ulna bone with the stature (58.8%), 5 articles in upper arm/humerus bone (29,4%), and 2 articles in hand length (11,8). Meanwhile, in lower extremity, 4 of 9 articles showed a strong correlation between tibia and fibula bone with stature (44,5%), 3 articles in femur bone (33,3%), and 2 articles in foot length (22,2%). Based on the measurement methods, 24 articles (96%) used percutaneus measurement, and only 1 article (4%) used post-mortem computed tomography (PMCT). This research concluded that all the components of extremity bones length have a significant correlation with stature, although its correlation is various. The best method is percutaneus measurement to avoid the potential bias occurred in imaging method.